Addiction Condition Watching Online Live Streaming Video - Aminah Daulay; Firman Firman; Netrawati Netrawati; Mohd Nazri (Universitas PGRI SUMATERA BARAT, 2025)
Addiction to viewing live online video games has become a big problem, with many students experiencing the detrimental effects of addiction to watching live online games streaming virtually every day. This reliance on watching live online video games needs to be avoided because it can interfere with daily living. The study's goal is to describe the condition of online video game addiction in pupils. In this study, 290 students were chosen at random using standard random sampling procedures. The addiction scale is used by the study instrument to watch live online video games. Using descriptive statistical tools and data analysis methodologies. The findings revealed that pupils with very low categories 22.07%, low category 19.31%, middle category 52.41%, high category 4.48% and very high category 1.72%.